Study on the Compliance Management of the Electricity Market in China Based on the Evolutionary Game Theory. (13th March 2021) - Jin, Luosong; He, Chang; Wang, Xiangyang; Wang, Wei; Zhao, Panting
Abstract : China's new round of power system reform has further released market vitality, making the power market more open and diversified. Meanwhile, China's power market faces various risks and challenges incurred by this new reform, which further highlights the importance of the compliance management. However, the study on effective compliance management of China's power market is missing, and the way to achieving effective compliance management is still unanswered. This paper tries to fill the research gap using the evolutionary game theory. We constructed a tripartite game model to analyze the strategic choices and influencing factors of power generators, compliance departments of the trading centre, and government regulatory agencies. Furthermore, simulation analysis was conducted based on evolutionary stable strategies. The results show that effective compliance management can be achieved without government supervision if the market mechanism is properly designed. In addition, the costs and profits of market participants and regulators are important factors influencing the effectiveness of compliance management. Our findings may arouse inspiration for the policy makers to construct an effective compliance management system.